1992
DOI: 10.1007/bf00120643
|View full text |Cite
|
Sign up to set email alerts
|

Applications of terpene analysis in forest genetics

Abstract: Application. Terpenoid compounds of conifers offer some advantages over other molecular markers and should be considered for use in fingerprinting genetic materials, measuring genetic diversity, selecting for resistance to pests, and determining systematic relationships and adaptation of species and races.Abstract. Terpenoid substances in forest trees are versatile biochemical systems for use as genetic markers and for studying genetic regulation at the biochemical level. Univariate, multivariate and correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 42 publications
7
44
0
1
Order By: Relevance
“…Chemosystematic studies, mainly in conifer tree species, have demonstrated that, although the total concentrations of terpenes are clearly influenced by the environment, the constitutive monoterpene profiles in mature organs are stable and little affected by environmental factors; therefore, terpenes have proven to be very useful as biochemical markers in plant genetics to characterize species, provenances, hybrids and clones (Baradat et al, 1991;Hanover, 1992;Elzinga et al, 2015;Barbero and Maffei, 2016).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Chemosystematic studies, mainly in conifer tree species, have demonstrated that, although the total concentrations of terpenes are clearly influenced by the environment, the constitutive monoterpene profiles in mature organs are stable and little affected by environmental factors; therefore, terpenes have proven to be very useful as biochemical markers in plant genetics to characterize species, provenances, hybrids and clones (Baradat et al, 1991;Hanover, 1992;Elzinga et al, 2015;Barbero and Maffei, 2016).…”
Section: Tablementioning
confidence: 99%
“…Although this contrasting response could be due to differences in experimental design between studies, i.e., greenhouse pot vs field experiments, sampling time, and different ages of the plants, another possible explanation is that plant chemical defences can vary with plant ontogeny. Under the selective impacts of herbivores, trees during their juvenile-to-mature transition process can promote changes in terpene mixtures to reduce the incidence of pest and diseases (Hanover, 1992;Boege and Marquis, 2005).…”
Section: Tablementioning
confidence: 99%
“…The relative proportions (percentages) of constitutive monoterpenes in mature tissues (which make up the constitutive monoterpene profile or the constitutive mixture) are strongly inherited, while the yeld ofmonoterpenes is subjected more to environmental parameters (Baradat eta/., 1991;Hanover, 1992;Plomion et a/., 1996). Correlations due to constraint are present when monoterpene proportions are used.…”
Section: Diterpenesmentioning
confidence: 99%
“…Genes involved in terpenoid biosynthesis may be turned "on" or "oft'', or regulated during organ development and growth phases of the tree (Hanover, 1992), and recently some changes in monoterpene expression have been related to seasonal periods of herbivores (see below).…”
Section: Diterpenesmentioning
confidence: 99%
“…The monoterpenes of Pinus spp. are dependent upon the plant genotype and can be used as biochemical markers in many genetic experiments and ecological studies [2,4,6,11]. The study of these compounds is mainly carried out in needles because the epithelium of their resin canals is the basic tissue responsible for the production of terpenes; however cortical monoterpenes are considered more stable [2] because foliar monoterpenes are related to the age of the needle.…”
Section: Introductionmentioning
confidence: 99%